A Comprehensive Review of Metabolite - Dr. V. Basil Hans (Emerging Trends in Metabolites, 2025)
Metabolites, tiny chemicals, are essential to physiology, signalling, and biological function. This extensive review classifies metabolites into primary and secondary categories by biological relevance. Alkaloids, flavonoids, and terpenoids contribute to ecological interactions and defence systems, while amino acids, nucleotides, and carbohydrates directly affect development and cellular function. The article examines metabolic pathways, mass spectrometry, NMR, and metabolomics, a growing field. Metabolites play a crucial role in various scientific and practical fields, including drug discovery, disease diagnosis, and agricultural improvement. According to the review, these small molecules offer valuable insights into biological pathways, enabling researchers to better understand disease mechanisms and identify potential therapeutic targets. In agriculture, metabolite profiling can help enhance crop yield, stress resistance, and nutritional value. The review also highlights the current challenges in metabolomics research, such as data complexity and variability, and stresses the importance of adopting integrative, multi-omics approaches to gain a more comprehensive understanding of cellular metabolism. Looking ahead, advancements in analytical technologies and computational tools are expected to further expand the scope and impact of metabolite research across disciplines.
Keywords: Primary and secondary metabolites; analytical methods; metabolic pathways; metabolomics